CyberKnife Boost for Patients with Cervical Cancer Unable to Undergo Brachytherapy - Haas, Jonathan A.; Witten, Matthew R.; Clancey, Owen; Episcopia, Karen; Accordino, Diane; Chalas, Eva (Frontiers in Oncology, 2012)
Standard radiation therapy for patients undergoing primary chemosensitized radiation for carcinomas of the cervix usually consists of external beam radiation followed by an intracavitary brachytherapy boost. On occasion, the brachytherapy boost cannot be performed due to unusual anatomy or because of coexisting medical conditions. We examined the safety and efficacy of using CyberKnife SBRT as a boost to the cervix after external beam radiation in those patients unable to have brachytherapy to give a more effective dose to the cervix than with conventional external beam radiation alone. Six consecutive patients with anatomic or medical conditions precluding a tandem and ovoid boost were treated with combined external beam radiation and CyberKnife boost to the cervix. Five patients received 45 Gy to the pelvis with serial IMRT boost to the uterus and cervix to a dose of 61.2 Gy. These 4 patients received an SBRT boost to the cervix to a dose of 20 Gy in 5 fractions of 4 Gy each. One patient was treated to the pelvis to a dose of 45 Gy with an external beam boost to the uterus and cervix to a dose of 50.4 Gy. This patient received an SBRT boost to the cervix to a dose of 19.5 Gy in 3 fractions of 6.5 Gy. Five percent volumes of the bladder and rectum were kept to < 75 Gy in all patients (i.e. V75Gy < 5%). All of the patients remain locally controlled with no evidence of disease following treatment. Grade 1 diarrhea occurred in 4/6 patients during the conventional external beam radiation. There has been no grade 3 or 4 rectal or bladder toxicity. There were no toxicities observed following SBRT boost. At a median follow-up of 14 months, CyberKnife radiosurgical boost is well tolerated and efficacious in providing a boost to patients with cervix cancer who are unable to undergo brachytherapy boost. Further follow-up is required to see if these results remain durable.